The Role of Transformational Leadership in Intellectual Stimulation of The Curriculum In Educational Institutions - Aprilia, Holifah (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study examines the role of transformational leadership in stimulating teachers' intellectuality in curriculum development in Islamic educational institutions, especially in SMA Nurul Jadid. The main focus of this study is how the principal as a leader can build a culture of critical, reflective, and innovative thinking through participatory and visionary leadership strategies. This study uses an approach where the results of the study show that the role of the principal is very influential in creating a learning ecosystem that encourages teachers to be actively involved in curriculum development. Three main findings that support the intellectual stimulation process are: a culture of criticism and reflection that is systematically facilitated, a curriculum mentoring program between teachers that strengthens professional collaboration, and the provision of access to information that supports knowledge renewal. These three aspects show that transformational leadership is symbolic and has practical implications in improving the quality of the curriculum based on values and the needs of the times. This study makes an important contribution to the development of leadership theory in Islamic education and recommends strengthening leadership capacity based on continuous learning